Shared Decision‐Making During Inpatient Rounds: Opportunities for Improvement in Patient Engagement and Communication. Issue 7 (5th February 2018) - Blankenburg, Rebecca; Hilton, Joan F.; Yuan, Patrick; Rennke, Stephanie; Monash, Brad; Harman, Stephanie M.; Sakai, Debbie S.; Hosamani, Poonam; Khan, Adeena; Chua, Ian; Huynh, Eric; Shieh, Lisa; et al.
Abstract : BACKGROUND: Shared decision‐making (SDM) improves patient engagement and may improve outpatient health outcomes. Little is known about inpatient SDM. OBJECTIVE: To assess overall quality, provider behaviors, and contextual predictors of SDM during inpatient rounds on medicine and pediatrics hospitalist services. DESIGN: A 12‐week, cross‐sectional, single‐blinded observational study of team SDM behaviors during rounds, followed by semistructured patient interviews. SETTING: Two large quaternary care academic medical centers. PARTICIPANTS: Thirty‐five inpatient teams (18 medicine, 17 pediatrics) and 254 unique patient encounters (117 medicine, 137 pediatrics). INTERVENTION: Observational study. MEASUREMENTS: We used a 9‐item Rochester Participatory Decision‐Making Scale (RPAD) measured team‐level SDM behaviors. Same‐day interviews using a modified RPAD assessed patient perceptions of SDM. RESULTS: Characteristics associated with increased SDM in the multivariate analysis included the following: service, patient gender, timing of rounds during patient's hospital stay, and amount of time rounding per patient ( P < .05). The most frequently observed behaviors across all services included explaining the clinical issue and matching medical language to the patient's level of understanding. The least frequently observed behaviors included checking understanding of the patient's point of view, examining barriers to follow‐through, and asking if the patient has any questions. Patients and guardians had substantially higher ratings for SDM quality compared to peer observers (7.2 vs 4.4 out of 9). CONCLUSIONS: Important opportunities exist to improve inpatient SDM. Team size, number of learners, patient census, and type of decision being made did not affect SDM, suggesting that even large, busy services can perform SDM if properly trained.